Давні міста у відеоіграх: культура відтворення і сприйняття - Плахін, Іван Максимович; Plakhin, I. M. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Бакалаврська робота присвячена вивченню репрезентації давніх міст у відеоіграх та впливу цих образів на формування історичної уяви гравців.

The bachelor’s thesis explores the representation of ancient cities in video games and the impact of these virtual images on the formation of historical imagination.
Ancient Cities in Video Games: The Culture of Simulation and Perception
Керівник роботи : Чорний Дмитро Миколайович – доктор історичних наук, професор
Keywords: HUMANITIES and RELIGION::History and philosophy subjects; HUMANITIES and RELIGION::Aesthetic subjects; відеоігри; давні міста; репрезентація минулого; гравецьке сприйняття; video games; ancient cities; representation of the past; player perception